La production animale au Mali central: Donnees sur les effectifs ovins et caprins eleves dans le cadre du systeme traditionnel, base pour l'etude comparative de deux methodes de collecte de donnees - Kolff, H.E. (CIPEA, 1983)
Summarises results of an inquiry survey of age & sex structure, reproductive performance, mortality & offtake in traditionally managed goat & sheep flocks around Niono, Mali, comparing results with those obtained w. longterm observations of same parameters in order to determine usefulness & interpretations of unique surveys.